The Accuracy of Initial Trust Judgments - Campagna, Rachel (2011)
This dissertation is dedicated to answer the questions: are we able to achieve accuracy in our initial trust perceptions: study 1) and what mechanism may account for this accuracy: study 2)? The first study conducted was field based, using temporary student teams. I used the social relations model: SRM) to determine how trust perceptions shift over time relative to individual and team perceptions. I found that individuals' perceptions remain moderately consistent over time and calibrated with their teams' perception only in terms of integrity perceptions. Further, individuals were able to achieve meta-accuracy: I know how much you trust me ) at both the generalized and dyadic levels. The second study was conducted in an experimental laboratory, examining trust at the dyadic level within a negotiation context. The perceivers': trustors) trust perceptions were manipulated based on false feedback regarding their partners': targets or trustees) response to a survey examining their perspective on the use of ethical negotiation tactics. I found that individuals' initial perceptions were correlated with their post-negotiation trust perceptions, partially mediated by the perceivers trusting behaviors and the targets' trustworthy behavior. The initial trust manipulation, however did not have an influence on the negotiated outcomes nor the second stage game. The results of study two support the notion that trust is a self-fulfilling prophecy